Production and Characterization of Pulp and Nanofibrillated Cellulose from Selected Tropical Plants. Issue 5 (4th May 2022) - Stanislas, Tido Tiwa; Tendo, Josepha Foba; Ojo, Emeso Beckley; Ngasoh, Odette Fayen; Onwualu, Peter Azikiwe; Njeugna, Ebenezer; Junior, Holmer Savastano
ABSTRACT: The goal of this study was to explore the feasibility of production of cellulosic pulp and nanofibrillated cellulose (NFC) from prevalent plants in west and central Africa; raffia fiber ( Raphia vinifera ), cassava bagasse ( Manihot esculenta ) and ambarella ( Spondias dulcis ); in order to assess their suitability as source of reinforcing elements for composite. Fibers were produced using both organosolv and basic soda methods to evaluate the effect of processing on fiber properties. The morphological characterization showed pulp fibers of width 24–33 µm and length 0.2–1.1 mm while nanofibers of width 110–278 nm were obtained after nanofibrillation. FTIR confirmed that the isolation processes effectively removed amorphous content (lignin and hemicellulose) while X-ray Diffraction analysis demonstrated the increase in crystallinity when fibers were processed from pulp to nanofibrillated cellulose. Despite being fibrous in nature, ambarella did not respond to soda and organosolv pulping possibly due to high wax (18.87%) and ash (16.05%) content. The yield of raffia pulp is within the range found in conventional wood sources. The nanosize nature, high specific surface area and aspect ratio, biodegradability and renewability of nanofibrillated cellulose have demonstrated the potential of raffia fibers and cassava bagasse as suitable sources for micro/nanocellulose.